Faktor-Faktor Mutu Pelayanan Kebidanan yang Mempengaruhi Tingkat Kepuasan Pasien di Poli Kebidanan RSUD Wonosari - Esthi, Franata Suriana; Mindarsih, Eko; Murni, Murni (Poltekkes Kemenkes Yogyakarta, 2017)
Hospitals play a role in improving the quality of health services. It was important to accurately measure patients' level of satisfaction.The previous study showed the score of 74.67%. It was lower than the level of customer satisfaction in Wonosari Regional PublicHospital (75.34%), 62.5% of the patients were satisfied of tangibles, 75% were satisfied on reliability, and 62.5% were satisfied inempathy. Research objective to investigate factors of midwifery service quality in Wonosari Regional Public Hospital MidwiferyClinic. This research method used analytical survey with cross sectional approach. 82 people were taken as samples by usingpurposive sampling technique. The data analysis employed Gamma testing. The result was factors of service quality in WonosariRegional Public Hospital Midwifery Clinicwere categorized as good. The percentages are: direct proof 54.9%, reliability 56.1%,empathy 57.3%, responsiveness 54.9%, guarantee 52.4%. The patient satisfaction level was 61.0%. The Gamma test resultshowed that the p-value of direct proof, reliability, empathy, responsiveness, and guarantee is 0.000 < 0.05. In addition, the value of rgamma of direct proof and responsiveness = 0.979, reliability = 0.993, empathy = 0.985 and guarantee = 0.988.